KETAHANAN KINERJA KEUANGAN EMITEN AGRIBISNIS DI TENGAH ESKALASI GEOPOLITIK TIMUR TENGAH PADA PT BISI INTERNATIONAL TBK - Hanalia Prameswary; Hari Purnomo (JURNAL LENTERA BISNIS, 2026)
This study aims to analyze the impact of the escalation of the United States-Israel-Iran conflict on the financial performance of PT BISI International Tbk as an agribusiness issuer listed on the Indonesia Stock Exchange. Geopolitical conflict in the Middle East may create pressure on the Indonesian capital market through rising energy prices, exchange rate depreciation, supply chain disruption, and shifts in investor sentiment. This study uses a descriptive qualitative method with a case study approach. The data were obtained from the listed company profile published by the Indonesia Stock Exchange, annual reports, consolidated financial statements of PT BISI International Tbk, and 20 local journal references published within the last five years. The findings indicate that geopolitical risk may affect BISI’s financial performance through higher operating costs, pressure on profit margins, and changes in market perception toward agribusiness stocks. This study recommends strengthening risk management, improving cost efficiency, diversifying supply chains, and applying fundamental analysis in investment decision-making for stakeholders in the Indonesian capital market